A modified rule for estimating notch root strains in ball defects existing in coiled tubing. (April 2022) - Ishak, Joanne; Badr, Elie A.
Highlights: The g n factor in Neuber's equation is not constant as suggested by Neuber's rule and Glinka's approach. The effect of ball defect depth is more significant on the magnitude of cyclic strains then the defect radius. A new proposed modification to Neuber's rule was proved to accurately predict the cyclic strains at the root of ball defects in coiled tubing. Abstract: Coiled tubing life is predominantly limited by fatigue as it undergoes cyclic bending strains well into the plastic regime leading to cyclic ratchetting due to plastic strain accumulation. Furthermore, small defects occurring in the oil field environment are capable of reducing coiled tubing fatigue life significantly. Small defects are macroscopic flaws that have small dimensions relative to the tubing wall thickness. Very shallow flaws at depths of only a few percent of the wall thickness can have a substantial, detrimental influence on fatigue life. Accordingly, the influence of surface ball defects on the magnitude of the fluctuating strains at the root of these defects was the subject of this investigation. Accurate cyclic strain magnitude predictions are essential to ultimately quantify the fatigue life of coiled tubing. The effects of defect radius and depth were both studied, and the strains at the notch root were evaluated for coiled tubing having a diameter of 2.375 in. and a wall thickness of 0.156 in.. A matrix of ball defects with various depths and radii were examined. The defects were introduced at the surface of a model having the same thickness as the actual coiled tubing. The FEA results provided detailed information about the magnitude of cyclic strains at the root of a defect in coiled tubing that were previously unavailable. The notch root strain results were used to bring about a modified Neuber's rule since conventional notch strain analysis approaches did not lead to accurate notch root strain range predictions. A new modified rule was therefore proposed and validated based on a detailed statistical analysis. This modified rule led to a substantial reduction in the percentage difference between the numerical notch root strain range and the estimated analytical one to within 8%.